2018
DOI: 10.1037/hea0000653
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and health-related quality of life in children and adolescents: A systematic review and meta-analysis.

Abstract: Physical activity is associated with broad physical and psychological benefits in children and adolescents. One construct which may universally characterize functioning across various pediatric populations is health-related quality of life (HRQOL). A number of studies have found positive associations between physical activity and HRQOL; however, to date no systematic review and meta-analysis of physical activity and HRQOL has successfully quantified effects in children and adolescents. A systematic search of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
149
2
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(171 citation statements)
references
References 103 publications
14
149
2
6
Order By: Relevance
“…Adequate sleep has been associated with better HRQoL [ 9 ]. Additionally, recent reviews showed that physical activity [ 6 , 10 , 11 ] and screen time [ 12 ] have been positively and negatively related to HRQoL, respectively, and sports practice has shown to be even better for some of its dimensions [ 10 ]. Furthermore, a Mediterranean diet pattern has been related to increased HRQoL scores [ 6 , 13 ], and alcohol [ 14 , 15 , 16 ], tobacco [ 17 ], and illicit drug [ 15 , 16 ] use seem to be negatively related to HRQoL.…”
Section: Introductionmentioning
confidence: 99%
“…Adequate sleep has been associated with better HRQoL [ 9 ]. Additionally, recent reviews showed that physical activity [ 6 , 10 , 11 ] and screen time [ 12 ] have been positively and negatively related to HRQoL, respectively, and sports practice has shown to be even better for some of its dimensions [ 10 ]. Furthermore, a Mediterranean diet pattern has been related to increased HRQoL scores [ 6 , 13 ], and alcohol [ 14 , 15 , 16 ], tobacco [ 17 ], and illicit drug [ 15 , 16 ] use seem to be negatively related to HRQoL.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above, it seems clear that higher levels of physical activity are related to greater levels of HRQoL and overall health benefits [22,25,26]. In fact, different studies have shown the benefits of regular physical activity on health and symptoms of people with ADHD [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…There are many factors that can modulate the relationships between exercise and psychosocial development. Although the type of design used in this research cannot explain causal relationships, it is considered that adequate contexts of physical exercise would generate environments in children and adolescents in which they have to overcome challenges and adapt to different situations, they could acquire greater sensations of competition, a better perception of body image or of their state of health [2,28,31,32]. In other words, exercise would contribute to acquiring a series of personal and social skills that would constitute an extrapolable advantage to other contexts, improving their psychosocial aptitude and capacity to adapt to the continuous demands of their social environment [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the regular practice of physical and sporting activity, carried out in appropriate social contexts, has been positively associated with other psychological parameters that could also have a favorable impact on child and adolescent development [26][27][28][29][30]. Thus, physical exercise usually occurs in environments that require the development of psychosocial skills necessary to function properly in them, which facilitates their training and learning, while contributing to interpersonal bonds or to the development of personal and social identity [2,26,31,32]. For this reason, the regular practice of exercise could contribute to improving the psychosocial functioning of children and adolescents, influencing aspects such as perceptions of self-concept, personal effectiveness or the assessment of one's own health [33,34].…”
Section: Introductionmentioning
confidence: 99%